Exploring the influences of news media on policy the case of the Migrant Workers and Overseas Filipinos Act (RA 8042) and the Overseas Absentee Voting Act (RA 9189) - Agbisit, Joanne B. 1974- (2007)
"One of society's most widely-held assumptions is that the press is among the institutions that move and shape public policies. This research validates this premise by examining the extent to which the Philippine news media contributed to the passage of the Migrant Workers and Overseas Filipinos Act (RA 8042) as well as the Overseas Absentee Voting Act (RA 9189), Using contact analysis, the research specifically looked at how the media covered issues prior to the crafting og the laws, and --using a combination of content analysis, archival research and interviews--established whether the coverage influenced the legislative agenda of the Philippine Congress and shapes the content of the laws. Findings showed that media's heavy coverage of labor migration issues and the recurrent framing og actors, e.g., migrant workers as "victims and heroes" and Philippine government as "negligent and ineffectual", propelled legislators into action and affected the framing of the Migrant Workers and Overseas Filipinos Act. On the other hand, the study found little evidence of media of media influence on the passage of the Overseas Absentee Voting Act. Media's heavy dependence on legislators as news sources shows that the legislators controlled and led the media discussion of overseas absentee voting issues. The study recommends the conduct of more systematic researches to unravel the highly complex media-policy interaction. Among the possible areas of study are: media's role in the passage of "midnight laws" vis-a-vis the passage of more protracted policies: media's coverage of and impact on policy implementation, evaluation and reform; and factors that shape or drive media agenda and frames."